2017
DOI: 10.1016/j.jaim.2016.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenol-rich fraction of Parquetina nigrescens mitigates dichlorvos-induced neurotoxicity and apoptosis

Abstract: BackgroundParquetina nigrescens (Afzel.) Bullock of the family Asclepiadaceae is known for its antioxidant effects with wide range of uses in Southwestern Nigeria especially in traditional medicine. This study was undertaken to explore if polyphenol-rich fraction (prf) from P. nigrescens will ameliorate dichlorvos-induced neurotoxicity and apoptosis. The exploration utilized evaluation of markers of oxidative stress, apoptosis and serum acetylcholinesterase (AchE) levels.MethodsForty Wistar rats randomly place… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…Some of its isolated chemical constituents reported include strophanthidin, strophanthidin glycoside, cymarin and Isorhoifolin [15,25]. The chloroform soluble extract of the leaves was reported to ameliorate dichlorvos-induced cardio-and nephrotoxicity, neurotoxicity, oxidative stress and apoptosis in rats [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Some of its isolated chemical constituents reported include strophanthidin, strophanthidin glycoside, cymarin and Isorhoifolin [15,25]. The chloroform soluble extract of the leaves was reported to ameliorate dichlorvos-induced cardio-and nephrotoxicity, neurotoxicity, oxidative stress and apoptosis in rats [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the DDVP-induced oxidative stress that resulted in the activities of catalase, SOD and GPx in the hippocampus, striatum, and prefrontal cortex of rats coupled with the increase in level of H 2 O 2 in the present study is an indication of oxidative damage suggesting impairment of the antioxidant status. Ajiboye [69] and Sharma and Singh [70] reported a similar decrease in the activities of catalase and SOD in the brain of rats following DDVP intoxication, while Ojo et al [14] and Ochigbo et al [71] reported the decreased activity of GPx in the brain of rats exposed to DDVP. The restoration in the activities of catalase, SOD and GPx in the hippocampus, striatum, and prefrontal cortex of rats as well as the level of H 2 O 2 suggest the chemoprotective potential of Q3G-RF by suppressing lipid peroxidation in the brain tissues.…”
Section: Discussionmentioning
confidence: 80%
“…The pulverized stem bark is applied to the skin surface to treat wounds and rheumatism. The leaf sap is used to treat jaundice and conjunctivitis [ 31 ]. The latex and leaf sap are externally used to treat burns and abscesses, applied to thorns in the skin to extract them [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…Jaundice and conjunctivitis [31] Latex White, hardening to black Arrow poison for hunting bush meat and production of black rubber [33] source: Summary of claim traditional uses of parts of the plant was generated by Authors'.…”
Section: Milky Fuidmentioning
confidence: 99%